World Bank East Asia and Pacific Economic Update, October 2018 : Navigating Uncertainty - World Bank (Washington, DC: World Bank, 2018)
Growth in developing East Asia and Pacific (EAP) was resilient during the first half of 2018. Although the external environment has become less favorable in some respects, the outlook for the region remains positive. After peaking in 2017, growth in developing EAP is expected to slow modestly in 2018, primarily reflecting the continued moderation in China’s economic expansion as its economy continues to rebalance. However, heightened uncertainty has intensified the risks to the region’s outlook. An escalation in trade tensions and heightened financial market turbulence, either due to an acceleration in U.S. monetary policy normalization or contagion from other emerging markets could threaten the region’s growth prospects. To navigate uncertainty, regional economies should reduce short-term vulnerabilities and enhance buffers, redouble their commitment to an open, rules-based international trade and investment framework, including through deeper regional economic integration, and deepen structural reforms. The intensification of risks underscores the need to continue to enhance economic security and promote economic mobility by: expanding and strengthening social assistance and insurance programs; investing in prenatal and early childhood development; and reducing gaps in educational access and quality for disadvantaged groups and in lagging areas.